Video-assisted Treatment of Rectal Fistulas: the Experience and Treatment Results - Groshilin, Vitalii S.; Brizhak, Viktoria G.; Khoronko, Evgeny Y.; Tsygankov, Petr V.; Khoronko, Yuri V. (Lietuvos chirurgija, 2020)
Aim. Evaluation of the effectiveness and identification of the benefits of a video-assisted fistula treatment method using fistuloscopy, in comparison with traditional methods of surgical treatment of complex forms of chronic paraproctitis, trans- and extrasphincteric, relapsing rectal fistulas. Patients and methods. A complex analysis of the results of surgical treatment was carried out in 228 patients with chronic paraproctitis, transphincteric, ectrasphincteric, including recurrent rectal fistulas, divided into three groups (main and two control), depending on the surgical methods of chronic paraproctitis used. Results. The result of surgical treatment of pararectal fistulas in the three study groups was compared. The effectiveness of treatment was assessed by the results of immediate and long-term postoperative period. It has been established that the use of a video-assisted fistula treatment method using fistuloscopy excludes the presence of an extensive postoperative wound in the perianal region, which significantly reduces the likelihood of its secondary infection, and the sphincter trauma, and in fact virtually eliminates its insufficiency. The use of video-assisted method of treatment of fistulas made it possible to reduce the number of postoperative complications. Conclusion. The final results (92.7% of favorable outcomes) allow us to recommend a video-assisted treatment for fistulas for wide practical implementation.